Hybrid Kerr-electro-optic frequency combs on thin-film lithium niobate - Yunxiang Song; Yaowen Hu; Marko Lončar; Kiyoul Yang (Light: Science & Applications)
Abstract Optical frequency combs are indispensable links between the optical and microwave domains. Chip-scale integration promises compact, scalable, and power-efficient frequency comb sources, enabled by the resonantly-enhanced Kerr effect or the electro-optic effect. While combs utilizing the former can reach octave-spanning bandwidths, and combs based on the latter can feature microwave-rate spacings, achieving both features at the same time has been challenging. Here, we simultaneously leverage the strong Kerr and electro-optic effects on thin-film lithium niobate, where dissipative Kerr soliton generation is followed by electro-optic phase modulation, to realize an integrated frequency comb reference with 2,589 lines spaced by 29.308 GHz and spanning 75.9 THz (588 nm). Further, we demonstrate electronic stabilization and control of the comb spacing, naturally facilitated by this approach. The broadband, microwave-rate frequency comb in our work overcomes the spacing-span tradeoff that exists in nonlinear integrated frequency comb sources, paving the way towards chip-scale solutions for next-generation laser spectroscopy, microwave and millimeter wave synthesis, as well as optical communications.